The outcome in relation to the treatment of patients with acute ST elevated myocardial infarction in whom more than 12 hours and less than 48 hours have passed since the onset of symptoms.: Treatment in relation to the treatment of patients with acute STEMI - Ivanović, Vladimir; Grgur, Jelena; Dabović, Dragana; Petrović, Milovan; Stojšić-Milosavljević, Anastazija; Bjelobrk, Marija; Čanković, Milenko; Stefanović, Maja (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Introduction. Patients in whom more than 12 hours have passed since the onset of symptoms, according to anamnestic data, represent late presenters of acute myocardial infarctionMethod. The study included 130 patients who were admitted because of the  acute STEMI from January to December  2017. Of these, 109 patients were treated with pPCI, while 21 patients were treated conservatively. Correlation was made between treatment outcomes, in-hospital mortality, one-year survival in relation to treatment, as well as risk factors and comorbidities.Results. There was a statistically significant difference in outcome compared to treatment (x2 = 7.119, p = 0.017). 8.3% of patients treated with pPCI were died, while 28.6% of patients treated conservatively were died.  Statistically significant difference (t = 9.385; p = 0.005) was observed in terms of treatment outcome and diabetes mellitus.Conclusion. Clinical, hemodynamic status and the presence of life-threatening arrhythmias should be considered when making treatment decisions.
Keywords: Acute myocardial infarction, primary percutaneous coronary intervention, medical treatment, outcome